The Correlation Between Anxiety Levels and Blood Sugar Levels in Elderly People in Malang City - Hannah, Nisa' Daril; Yuliadarwati, Nungki Marlian; Rahmawati, Nurul Aini (Universitas Muhammadiyah Surakarta, 2026)
Introduction: Anxiety is a common mental health problem among elderly and can affect physiological conditions, including blood glucose levels. This study aims to analyze the relationship between anxiety levels and random blood glucose levels in elderly in Malang City. Methods: An analytical observational study with cross-sectional approach involved 68 elderly respondents aged ≥60 years from three nursing homes in Malang City using purposive sampling technique. Anxiety levels were measured using Geriatric Anxiety Scale (GAS) questionnaire and random blood glucose levels using glucometer. Data were analyzed using Spearman's Rho correlation test. Results: Majority of respondents were aged 70-79 years (41%) and male (53%). Anxiety levels showed 46% moderate anxiety, 35% severe anxiety, and 19% mild anxiety. Random blood glucose levels showed 68% prediabetes category and 32% normal. Spearman's Rho correlation test resulted in correlation coefficient r=0.560 with significance value p=0.000 (p<0.05), indicating significant positive relationship. Conclusion: There is a significant positive relationship between anxiety levels and random blood glucose levels in elderly in Malang City. The higher the anxiety level, the higher the random blood glucose level.